The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1039/b809117j
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of drug metabolites and cytotoxicity assay simultaneously using an integrated microfluidic device

Abstract: An integrated microfluidic device was developed for the characterization of drug metabolites and a cytotoxicity assay simultaneously. The multi-layer device was composed of a quartz substrate with embedded separation microchannels and a perforated three-microwell array containing sol-gel bioreactors of human liver microsome (HLM), and two PDMS layers. By aligning the microwell array on the quartz substrate with cell culture chambers on the bottom PDMS layer, drug metabolism studies related to functional units,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 28 publications
2
79
0
1
Order By: Relevance
“…Prot et al 31 determined first deteriorations of cell proliferation at 1 mM APAP within their respective microfluidic biochip cultivation system. In another microfluidic biochip used by Ma et al, 19 the viability was reduced to 30% with an APAP concentration of 10 mM which is similar to the results of our study. Xia et al 32 observed that the cells grown in a laminar flow perfusion bioreactor were more sensitive for APAPinduced hepatotoxicity than the cells grown in a static 2D culture, and 60% of cell death was shown after 24 h of treatment with 25 mM of APAP.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Prot et al 31 determined first deteriorations of cell proliferation at 1 mM APAP within their respective microfluidic biochip cultivation system. In another microfluidic biochip used by Ma et al, 19 the viability was reduced to 30% with an APAP concentration of 10 mM which is similar to the results of our study. Xia et al 32 observed that the cells grown in a laminar flow perfusion bioreactor were more sensitive for APAPinduced hepatotoxicity than the cells grown in a static 2D culture, and 60% of cell death was shown after 24 h of treatment with 25 mM of APAP.…”
Section: Discussionsupporting
confidence: 82%
“…4 Furthermore, different microfluidic systems have been developed in the past in which constant growth conditions were achieved by a perfusion flow of cell culture medium providing permanent sustenance with nutrients and oxygen as well as removal of waste metabolites. 18,19 However, to our knowledge, there is still no system described where hepatocytes are cultivated with indirect flow without any physical barrier which would reflect the in vivo situation even better. In order to establish a useful cultivation system for the analysis of hepatocellular functions, we tested the growth, differentiation, and metabolical behavior of HepG2 cells embedded in Matrigel in the OrganoPlate from MIMETAS and Leiden University that combines these unique characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that conventional macroscopic assays for drug development are still widely used, microfluidic technology has attracted increasing interest in the past years (Nguyen et al 2013;Abkarian et al 2006;Dai et al 2010;Adamo et al 2012;Mao et al 2012;Ma et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…In a similar development, Ma et al [257] developed an integrated multi-layered microfluidic device composed of a quartz substrate with embedded separation microchannels and a perforated three-microwell array containing sol-gel bioreactors of human liver microsome (HLM), and two PDMS layers. The aim of the study was to simultaneously characterise drug metabolites and carry out a cytotoxicity assay.…”
Section: Drug and Toxicological Screeningmentioning
confidence: 99%